Foundations of physical activity and public health - Kohl, Harold W. III. 1960-; Murray, Tinker Dan 1951-; Salvo, Deborah 1983- (Champaign, IL Human Kinetics, 2020)
"This text defines the intersection of kinesiology and public health and will include the new 2018 Physical Activity Guidelines for Americans. It offers a solid introduction to the basic concepts of physical activity and the effects of physical activity as it relates to public health, and builds up this foundation by offering evidence-based strategies for increasing physical activity in individuals and populations"--
Includes bibliographical references and index.
Keywords: Exercise; Public health; Health promotion -- methods